Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Tiki Jalur Nugraha Ekakurir (JNE) Kcu Karawang - Rosgita, Rosgita; Ramdani, Danny (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to get empirical evidence. Explaining the phenomena, and making conclusions about the influence of work environment variables and work motivation on employee performance at PT. TIKI Jalan Nugraha Ekakurir (JNE) KCU Karawang. This study was conducted using descriptive and verification namely, knowing, explaining and analyzing. In this study, a sample of 206 where respondents were selected using random sampling. The research variables include independent variables, namely work environment (X1) and work motivation (X2), as well as employee performance variables as the dependent variable. Data analysis techniques used the Likert scale technique and path analysis using Microsoft Office tools and SPSS for Windows version 25. The results of this study prove that there is a correlation between Environment and Motivation 0.688. This means that the work environment and work motivation have a relationship with strong criteria. The partial results of hypothesis testing work environment variables do not significantly influence employee performance variables. There is a simultaneous influence between work environment and work motivation on employee performance at PT. TIKI NUgraha Ekakurir Route (JNE) KCU Karawang by 15.6%, while 27.9% is influenced by variables that have not been studied.